PARTIAL PRODUCTIVITY OF AGRICULTURE IN THE WESTERN BALKAN COUNTRIES – IMPLICATION FOR COMPETITIVENESS OF THE RURAL ECONOMY - Zekić, Stanislav; Gajić, Milivoj; Lovre, Koviljko (Economics of Agriculture, 2018)
The process of transition and, within it, the agricultural transformation in the Western Balkan countries resulted, in the first phase, in the weakening of the developmental performances in agriculture. Such tendencies widened the gap between the countries of the Western Balkans and the EU countries, which continued their steady increase in agricultural productivity. Unfavorable tendencies in agricultural productivity adversely affected its competitiveness, and, consequently, the competitiveness of the rural economy as a whole. The effect of the low agricultural competitiveness on the competitiveness of the rural economy is determined by the importance of agriculture in the rural economy, which is substantial in the West Balkan countries.